(3GdGfS GdLdjd aj JGQjN GdbOS hGdNdjds - (3YHO GdQMef Hf eMeO Hf YHO GdQMef GdoYndrjej GdMfHdj, nCoHh Gdojref, eLjQ GdOjf,J (B928 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Sgd Ydi Ndbg aJM CHhGH GdQMeI CeG HYO agPG eNJUQ GSJNQJ Gddg JYGdi ai LeYg jJVef JGQjN HjJ GdebOS s
(3BNQgG (B:s
(3hbVJ SfI JSYeGFI hcGfJ SfI TOjOI hcKjQI GdaJf hGdMQhH hbO GfJgi PcQ GdMhGOK GdhGbYI HGdbOS hGdNdjd s
(3HgG fXGe GdJYbjHIs
(3jdi GdeNWhW JQLeI ceGd GdOjf Ke Pjd Yfg GdcJGH ai CQHY hQbGJ jfJgi HPcQ GdhbYI HXGgQ GdTGe GdhQbI GdChdi cJHJ HNW eZGjQs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B177s
Keywords: (3GdJGQjNs